Hadith #1282 - Sahih al-Bukhari - Amir al-Sha'bi عامر الشعبي (Sahih al-Bukhari)
Ibn `Abbas (who was at that time a boy) said, “Allah’s Messenger (ﷺ) came to a grave and the people said, ‘He or she was buried yesterday.’ ” Ibn `Abbas added, “We aligned behind the Prophet (ﷺ) and he led the funeral prayer of the deceased.”
Grade: Sahih

Hadith #2484 - Sahih al-Bukhari - Amir al-Sha'bi عامر الشعبي (Sahih al-Bukhari)
I heard An-Nu`man bin Bashir on the pulpit saying, “My father gave me a gift but `Amra bint Rawaha (my mother) said that she would not agree to it unless he made Allah’s Messenger (ﷺ) as a witness to it. So, my father went to Allah’s Messenger (ﷺ) and said, ‘I have given a gift to my son from `Amra bint Rawaha, but she ordered me to make you as a witness to it, O Allah’s Messenger (ﷺ)!’ Allah’s Messenger (ﷺ) asked, ‘Have you given (the like of it) to everyone of your sons
Grade: Sahih

Hadith #4082 - Sahih al-Bukhari - Amir al-Sha'bi عامر الشعبي (Sahih al-Bukhari)
Whenever Ibn `Umar greeted the son of Ja`far, he used to say (to him), “Assalam ‘Alaika (i.e. peace be on you) O the son of two-winged person.”
Grade: Sahih